Reflections on the IASWG European Groupcamp in Birštonas, Lithuania - Baar-Kooij, Hilde; Bartusevičienė, Lina; Burneikaitė, Salomėja; Doel, Mark; Godvadas, Paulius; Liobikienė, Nijolė Teresė; Schmitz-Remberg, Tanja E; Tully, Greg; Vyšniauskytė-Rimkienė, Jorūnė (Groupwork, 2017)
Abstract: This article is written by multiple authors all of whom participated in a ‘Groupcamp’ (a residential experience for groupworkers about groupwork) in Birštonas, Lithuania, in October 2015. The purpose of the camp was to bring groupworkers together from various countries and with many different group approaches, but with a common desire to share their practices and to experience them directly. The Groupcamp in Lithuania honoured the work of Ann Bergart and her colleagues who have established an experiential Groupcamp in the US. Groupcamp allows those on the ‘factory floor’ to exchange knowledge directly through practical group experiences that transcend language and culture. The purpose of the paper is to give the reader a flavour of these experiences and to pass on some practical group exercises – their purposes, how they might be used and the reflections of those who experienced them. The paper reflects on the journey made by the various participants over the three days of the camp. Keywords: group work; groupwork; Groupcamp; IASWG; experiential learning; activities; improvisation